The Development of Ecosystem and Talent Cultivation of Lei Opera - Ye, Zhanxia; Feng zhao, Shu; Maneewattana, Chutima (Journal of Roi Kaensarn Academi, 2024)
The purposes of the research were to study The Development Ecosystem and Talent Cultivation of Lei Opera. The research methodology was qualitative research which takes the Lei Opera troupe organization as the main research object and adopts the field survey method to analyses and discuss the development and inheritance of Lei Opera. The research findings form the interview and observations showed that in recent years, the performance money of Lei Opera is still rising, and the lei opera performance market has shown a good momentum of continuous development. However, in the booming state of the performance market, it is worrying that the overall artistic level of Lei Opera has not improved too much in recent years, especially the overall level of lei opera actors is obviously behind the three operas of Cantonese opera, Chaozhou opera and Han opera. The main reasons for its existence: 1. The overall level of Lei Opera actors is not high, mainly due to the lack of artistic accumulation of drama and the poor family of drama, which is the biggest congenital deficiency of a young drama.2. The nature of the troupe leads to the stability of the troupe team; 3. The degree of systematization and standardization of the musical art system and performing art is relatively low.